Implementasi Regulasi dan Desain Kontrak Rahn (Gadai Syariah) Pada Lembaga Keuangan Syariah (LKS): Tentiyo Suharto - Suharto Tentiyo (Program Studi Perbankan Syariah Jurusan Syariah, Ekonomi dan Bisnis Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal (STAIN MADINA), 2024)
Tentiyo Suharto Sekolah Tinggi Agama Islam Negeri Mandailing Natal Email: tentiyosuharto18@gmail.com, Abstract To meet the urgent needs of life which are growing rapidly nowadays, rahn (sharia pawn) is an important concept and is easy to use in various financial transactions. Rahn has a significant role in driving the economy and providing positive solutions for individuals and companies in meeting their financial needs. The method used in this research is a qualitative research method because the amount of data obtained from books and library data and the internet in the form of articles, journals, theses, theses, dissertations and other supporting scientific works is qualitative data. With the aim of implementing the operational concept and basic regulations of Rahn in Islamic financial institutions in Indonesia. The implementation of rahn in its operations is where rahin as (the customer) comes to the murtahin (shariah pawnshop institution) and enters into a contract by handing over marhun (collateral/Borg) as debt/financing coverage) to obtain marhun bih (loan or financing). Sharia pawnshops have a strong legal basis in Islam and have been used since the time of the Prophet Muhammad and national law in Indonesia. The rahn concept is based on sharia principles which prohibit the elements of riba (interest or additions in any form), Gharar (unclear/fraud) and Maysir (uncertainty/gambling) and encourages fairness and sustainability in healthy financial transactions. This concept allows individuals or companies to obtain financing by using valuable items as collateral (Borg) such as gold, diamonds, pearls, jewelry, vehicles, or electronics. Meanwhile, contract designs in sharia pawnshops that can be used in developing their business are by using the Qard (Loan without Return), Ba'I Al-Murabaha (Buy and Sell), Mudharabah (Profit Sharing System) and Ijarah (Rent) contracts. Pegadaian is an alternative for people who need fast funds for urgent or emergency needs, such as health, education, business or consumption costs and others. Keywords: Sharia Financial Institutions, Regulation, Islamic Law, Rahn,Qard, Bai al-Murabaha, Mudharabah, Ijarah, Guarantee.